Prótese com cantiléver suportada por um implante único na zona estética: uma nova abordagem terapêutica - Barreto, Mauricio Andrade (2010)
Background: Esthetic complications due to non harmonious periimplant soft tissue profiles are common in the anterior maxilla, especially when two adjacent implants are found. This controlled clinical studies evaluatied soft and hard tissue stability of a ten single implant supported cantiléver prosthesis. Methods: Ten patients, 5 men e 5 women, with absence of the maxillary central and lateral incisors were treated with a single implant supported cantilever prosthesis. The soft peri-implants tissues were assessed using the Pink Esthetic Score (PES) described by Fürhauser et al. Assessment of the level of peri-implant bone support were performed on radiographs taken 4 months after implant placement, but immediately before implant exposition (baseline), and at the 6-months follow-up (immediately after seating definitive prosthesis). Results: The Pink Esthetic Score (PES) based on clinical photographs obtained 1 week after seating definitive prosthesis is 9.25 (SD = 2.94). The crestal bone loss was 0.92mm (SD = 0.8) at 6-moth follow-up (immediately after seating definitive prosthesis). The crestal bone level changes for time interval was 1.42 mm (SD = 0.7). Conclusions: The single implant supported cantilever prosthesis can provide a more aesthetic appearance for the treatment of unilateral absence of upper central and lateral incisors. The single implant supported cantilever prosthesis was unable to avoid the loss of inter-implant bone crest. More long-term controlled clinical studies are needed to assess the stability of soft tissue and hard in this therapeutic modality as well as studies to evaluate its mechanical behavior.